Since 1948 : Israeli literature in the making - Berg, Nancy E.; Sokoloff, Naomi B. (Albany : SUNY Press, State University of New York, 2020)
"Argues for stretching the boundaries of Israeli literature linguistically, geographically, and generically"--
Introduction: Under construction : a kind of Festschrift for Israeli literature -- Part One. Through time : silences, voices, echoes -- Not one, but five moments of silence : on the poetics and politics of asking for silence -- Sounding the Mizrachi voice : Ḥafla thematics from the Ma'abarah to the post-Arabic novel -- Anthological poetics : reading Amichai and Halfi in liberal prayerbooks -- Part two. Across language and territory : literature and identity -- When Yiddish was young in Israel -- A Canaanite story : language, national identity, and the 1948 war -- Hebrew unbound : alternative homelands in the New World -- Part three. Between the lines : rethinking genres -- From here to elsewhere and back in Israeli-Hebrew children's literature -- "The pigs were my best friends" : animals and the Holocaust in Alona Frankel's memoirs -- Stalagim : at the limits of Israeli literature -- Part four. Concerning canons -- Disruptive nativity : the poetry of Rina Shani and the sixties in Israel -- Asaf Schurr and the critique of postmodernism in contemporary Hebrew literature -- "And the winner is . . ." : the economy of literary awards -- Appendix A: Canaanite story : "the lord be praised".
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Israeli literature -- History and criticism; Littérature israélienne -- Histoire et critique; Middle Eastern; Jewish; LITERARY CRITICISM; Jewish Studies; SOCIAL SCIENCE; Israeli literature; Electronic books; Criticism, interpretation, etc